EFFECT OF ELICITATION OF METHYL JASMONATE, SALICYLIC ACID AND CALLIETE IN LINKING WITH THEIR POST-TREATMENT CONTACT TIME ON ACCUMULATION OF PHENOLIC COMPOUNDS IN PINEAPPLE (ANANAS COMOSUS L.) - Désiré , N’GORAN Kouakou; Abou, YEO Navigué; Dramane, KONE; Hilaire, KOUAKOU Tanoh; Michel, ZOUZOU (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2022)
The aim of this study was to evaluate the effect of three elicitors on the biosynthesis of phenolic compounds in two pineapple cultivars as a function of incubation time. The cultivars Cayenne smooth and MD2 were used and their leaves were sprayed with different concentrations of methyl jasmonate, salicylic acid and calliete. For each concentration, several incubation times were evaluated and then the concentration combined with the incubation time of each elicitor that caused the greatest accumulation of phenolic compounds in the leaves was selected. The best combination of elicitors was determined by coupling them two by two. Thus, the phenolic compounds induced in the leaves of the two cultivars sprayed with the best elicitor combination were identified by HPLC. The results showed that MeJA resulted in the best accumulation of phenolic compounds for a concentration of 10 mM after an incubation time of 72 h, followed by 5 mM SA after an incubation time of 24 h and 5 mM Ca after 48 h of post-treatment. The best combination of elicitors was MeJA and Ca after 72 h incubation. NWP from the smooth Cayenne cultivar induced six (6) phenolic compounds while PTCa, PTM and PTMCa synthesized eight (8), ten (10) and twelve (12) phenolic compounds, respectively. NWP from cultivar MD2 induced eight (8) phenolic compounds while TPCa caused de novo synthesis of ferulic acid. PTM induced de novo pterosilbene and kaempferol in addition to those of PTCa whereas PTMCa induced in addition to those of PTM, quercetin synthesis. The elicitors thus increased the level of accumulation of phenolic compounds in the treated plants..